Sistem Pengukuran Kinerja Perusahaan Dengan Metode Capability Maturity Model - Stefany Oktavia Chandra (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2016)
This research will discuss the Company’s Performance Measurement Information System with the Method of the People Capability Maturity Model (Case Study at PT Kepuh Kencana Arum Makassar) is a system that can help the company tp conduct performance measurement in order to be a reference, in particular inter-company competition. By using people capability maturity model (P-CMM), then the system can measure the performance of companies using measurements of methods people capability maturity model (P-CMM). This study yield performance of each Division in the Billowing Kencana PT Arum Makassar in the result there are 2 divisions are at level 2 are junior operators and junior helper and also 2 divisions at level 3 that senior senior operator and helper.